PERAN SEKTOR UMKM DALAM MENGURANGI KEMISKINAN DAN MENUNJANG PERTUMBUHAN EKONOMI INDONESIA STUDI KASUS PROVINSI JAWA TIMUR PERIODE 2018-2023 - Samosir, Refani Abednego; Jhon Kristopel Manalu; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the role of the Micro, Small, and Medium Enterprises (MSMEs) sector in reducing poverty and supporting economic growth in East Java Province during the 2018-2023 period. The research employed a mixed-methods approach combining quantitative analysis of secondary data from the Central Bureau of Statistics (BPS), the East Java Provincial Office of Cooperatives and MSMEs, and the Ministry of Cooperatives and SMEs of the Republic of Indonesia, with qualitative analysis through interviews and policy document studies. The results show that MSMEs in East Java make a significant contribution to the economy, with an increase in contribution to Gross Regional Domestic Product (GRDP) from 58.3% in 2018 to 61.2% in 2023, while absorbing approximately 95% of the province's total workforce. Correlation analysis reveals a strong negative relationship between MSME labor absorption and poverty rates (correlation coefficient -0.87), where every 1% increase in MSME employment correlates with a 0.72% decrease in poverty. However, MSMEs still face major constraints including limited access to capital (only 23% have access to bank credit), low adoption of digital technology (35% have a presence in digital markets), suboptimal product quality, and limited market access. Government policies such as People's Business Credit (KUR), business capacity training, and licensing simplification have had positive impacts, but their effectiveness needs to be enhanced through more integrated policy coordination and sustainable mentoring. This study recommends improving access to capital, strengthening digital technology capacity, enhancing product quality, and expanding market access to optimize the role of MSMEs in poverty reduction and economic growth in East Java.